Alterações epigenéticas envolvidas na via de invasão trofoblástica na pré- eclâmpsia precoce e tardia - Juliana de Oliveira Cruz (2023)
Preeclampsia (PE) is defined as hypertension after the 20th gestational week and may be accompanied by proteinuria or damage to other target organs. PE can be classified according to the gestational age of onset of symptoms as early-onset (EOPE < 34 weeks of gestation) and late-onset (LOPE ≥ 34 weeks of gestation). However, it is unclear whether EOPE and LOPE have different etiologies and pathophysiology or result from a gradual process of the same condition. Abnormal placental development and poor trophoblastic invasion are primary factors in PE. Several epigenetic mechanisms participate in gene regulation and modulate cell development and differentiation. The objective of this work is to evaluate epigenetic changes in regulatory regions of genes involved in the trophoblastic invasion pathway in pregnant women with PE (EOPE, LOPE) and healthy pregnant women. In chapter 1, a systematic review was performed to identify differentially methylated genes in the placenta of pregnant women with PE and the pathways in which they are involved. We describe a significant difference in global DNA methylation (mDNA) between PE and control, and a pronounced effect on gene-specific mDNA in PE, especially in EOPE and premature PE. From these findings, we selected candidate genes for analysis of mDNA and gene expression in the placenta and peripheral blood of pregnant women with PE (EOPE and LOPE) and controls. In chapter 2, we present an analysis of TIMP3 gene methylation and expression in the placentas of pregnant women with EOPE and LOPE. We identified 28 differentially methylated probes in the TIMP3 gene promoter in PE, 38 in EOPE, 20 in LOPE, four in term PE compared to controls, and eight in EOPE compared to LOPE. Furthermore, we found hypomethylation of more than 70% in the comparison groups, and an increased expression of TIMP3 in samples from corresponding placentas of PE, EOPE, and LOPE compared to controls. These findings highlight the role of DNA methylation in the promoter region of the TIMP3 gene as an epigenetic mechanism involved in the pathophysiology of PE. In chapter 3, we present circulating TIMP3 levels in pregnant women with PE and controls. In the primary study, patients with PE and gestational hypertension exhibited increased concentrations of TIMP-3 protein compared to healthy pregnant women and non-pregnant women. These findings were confirmed in the replication study. No difference was found in TIMP-3 concentrations between EOPE and LOPE. Furthermore, TIMP-3 concentrations were significantly correlated with plasma concentrations of TIMP-1 and MMP-2 in PE. In Chapter 4, we show the epigenetic mechanisms that regulate the expression of the N-Terminal Truncated isoform of Matrix Metalloproteinase-2 (NTT-MMP-2), by activating a latent promoter located in the first intron of the MMP2 gene. We highlighted the recent findings on the presence of the NTT-MMP-2 isoform in renal dysfunction and heart disease. Given the above, we can conclude that epigenetic alterations in regulatory regions of genes that participate in the trophoblastic invasion pathway are related to the development of preeclampsia and its EOPE and LOPE subtypes.